Characterization of ripe empty fruit bunch (EFB) oil and waste frying oil on the properties of starch bio-based plastics - Ismail, Puteri Nadhirah (2019)
Much attention has been paid in recent years on research to replace petroleum-based commodity plastics with renewable materials in a cost-effective manner. The current study has therefore focused on the production of bio-plastic, primarily starch, from renewable materials. This paper presents the results of studies of the characteristics of the produced bio-plastic by using ripe empty fruit bunch (EFB) oil and waste frying oil (WFO). The potato starch-glycerol based with different amount of ripe EFB oil and waste oil (2.5, 5.0, 7.5 and 10.0 g) were prepared and drying at 40°C for 48 h. Mechanical properties, water solubility, water vapor permeability (WVP), biodegradation test and fourier transform infrared spectroscopy (FTIR) were performed in this study. As a result, the higher the amount of ripe (EFB) oil/WFO in starch bio-based plastic, increase the elasticity which the higher value is 16.5 MPa and 36.33% in elongation at break but decrease in tensile strength, solubility and water vapor permeability. FTIR exhibit that the intermolecular interaction in starch bio-based plastic occurred through C-O-H, O-H, C-H aliphatic and C=O groups. For biodegradation test, all starch bio-based plastic was no longer in soil after a week they were buried which means they have been degrade successfully.